Telepharmacy internship training to empower future pharmacists and healthcare professionals / Mahmathi Karuppannan ... [et al.] - Karuppannan, Mahmathi; Zulkifly, Hanis Hanum; Abdul Halim Zaki, Izzati; Mohd Noordin, Zakiah; Md Hussin, Nur Sabiha; Hamdan, Nor Elyzatul Akma; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2023)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), organised a telepharmacy internship training session on the 16th and 23rd of October 2023. This programme held at the Telepharmacy Laboratory at Level 4, FF3 Building, UiTM Puncak Alam, facilitated by six clinical pharmacy lecturers, offered an unparalleled learning experience for 79 students from both pharmacy and allied health sciences at San Pedro College (SPC), Davao, Philippines.